French Lexical Innovation in Moroccan Mediated Interactions - Mahtane, Hicham (Taikomoji kalbotyra, 2021)
The French language in Morocco seems to be an evolving research field for linguists and sociolinguists. In everyday chats, Moroccan speakers use a particular lexicon of French on a formal and informal semantic level without much concern for conformity with standard French.Based on a one-off observation of exchange situations, we carried out a qualitative descriptive analysis based on studying the form and meaning of neologisms in the mediated interactions of the users. This study demonstrated a great diversity of lexicon use in the atypical written speeches of Moroccan chatters as well as an important freedom of spelling in relation to standard. The language practices of these chatters testify creative vitality and dynamics of neologisms. It also appears that these practices perform expressive, playful, and ornamental functions.
Keywords: mediated interactions; neologism; lexical creativity; written speeches